Distribution of metals in fruits, vegetables and shellfish of Sabah - Muhammad Iqbal Hashmi (2002)
This thesis is divided into two parts the first part deals with the determination of various essential and toxic metals in tropical fruits and vegetables available in main markets and most frequently consumed by the major population of the city of Kota Kinabalu, Sabah. The second part deals with the determination of metals in two marine samples namely sea cucumber and tiger prawn. Besides these sea sediment and seawater collected from South China Sea in Kudat area were also analyzed. Tiger-prawn (shrimp) were obtained from locally cultured and bred in commercial ponds in Tuaran and Likas localities near Kota Kinabalu. The determination of metals in fruits, vegetables and marine samples was carried out using flame atomic absorption spectroscopy (FAAS). In general, the concentrations of the bulk metals such as sodium, potassium, magnesium and calcium were found to be present approximately in the same ratio both in vegetables and fruits. There concentrations are found to vary in the following order: potassium > magnesium > calcium > sodium. But the exact concentrations of potassium and magnesium are more in fruits than vegetables whereas calcium is more in vegetables than in fruits. The concentration of sodium is considerably low as compared with other bulk metals. On the basis of the average RDA, it may be concluded that fruits and vegetables can provide the required amounts of potassium and magnesium but calcium and sodium are required to be taken from other sources including mineral supplements. The levels of the majority micronutrient metals are found to be almost equally distributed among. fruits and vegetables grown in Sabah as are the toxic metals: lead and cadmium. Tiger-prawn (shrimp) were obtained from locally cultured and bred in commercial ponds in Tuaran and Likas localities near Kota Kinabalu were found to be contaminated with metals particularly cadmium, cobalt, chromium, iron, manganese, molybdenum, nickel, lead and zinc. The major causes of this was found to be environmental and anthropogenic activities in the area. The result from the analysis of sea cucumber, sea sediments and seawater revealed that concentration of metals particularly cadmium, cobalt, chromium, manganese, molybdenum, nickel, lead, and zinc exceeded those in the sea sediment and sea cucumber. The data suggest some kind of a physiological control in sea cucumber for metal profile in the body. This animal either uses a barrier against excessive uptake or eliminates the quantity in excess of body's capacity. Protein denaturation in beche-de-mer stored at low temperature was also studied because Sabah Malaysia is particularly famous for indigenous resources of this particular animal, mainy because of its nutritional and medicinal value. Since good breeding and culturing practice are not utilized resulting in the deterioration of the finished product. Of all the various temperature tested, chilling at -10°C was found to be the most effective means of controlling protein denaturation